Amelioration of Volcanic Soils from Camiguin Island (Southern Philippines) Using Natural Amendments - Boniao, Renato D. (2000)
Cultivated and uncultivated soils along the footslopes of Mt. Hibok-Hibok volcano, down to the nearby coastal areas were examined to assess the effects of cultivation on their chemical fertility characteristics. Some selected soils were incubated for 9 months with natural amendments (calcium silicate, ground basaltic pyroclastics, and peat) to determine whether addition of these materials can improve soil surface charge properties, particularly point of zero charge (pH,) and cation exchange capacity (CEC). Effects of adding the amendment materials on plant growth were investigated with maize as test crop in a glasshouse experiment. The results showed that cultivated soils have lower % organic carbon (O.C) content and subsequently lower CEC compared to the uncultivated ones. Cultivation also raised pH,. Adding peat reduced pH" increased the CEC, and improved their ion retention. Adding basaltic pyroclastics showed promise to improve the charge properties of the soils but as an amendment material, a longer incubation time was needed to detect some influence on the soil. Calcium silicate, on the other hand, gave an extremely high pH, and pH. The high values were presumably because the rate applied was too high, which resulted in silicic acid precipitation. Plant response to the amendments (peat and basalt pyroclastics) showed that nutrient uptake was positively related to an improved ion retention of the soils. It also showed that relative heights and weights were linearly correlated with cations concentration in the soil solution.